KEMASAN PINTAR BERBASIS EKSTRAK UBI UNGU SEBAGAI INDIKATOR KESEGARAN FILLET IKAN PATIN PADA SUHU CHILLER - Anisa Dewi Saraswati Saraswati; Rina Ningtyas Ningtyas (SAGU, 2021)
Dory fillets (Pangasius sp.) contains high fat and protein, that is prone to decay. To reduce this risk, cooling storage and packaging of dory fillets with freshness indicator to make it easier for consumers to recognize quality of the fish. This study aims to determine the color change of the indicator during the storage period, as well as to determine the correlation between the color change of the indicator label and the quality of dory fillets. Indicator labels are made using natural dyes from purple sweet potato extract. The purple sweet potato was extracted, then the pH varied (pH 2, 5, 8, and 11). The sensitivity of the solution to amine gas was tested using NH4OH. Indicator label testing was carried out by application to dory fillets, besides that, the L*, a*, b* value, fish pH, and organoleptic tests were carried out every 4 days for 12 days with 2 replications. The results of the sensitivity test showed that the indicator solution was sensitive and showed a color change to the NH3 vapor. Based on the measurement of L*, a*, b* values, variations in pH 2 and 5 produce significant color changes and accordance with the results of visual observations where the color of the label changes from pink and purple to light blue. Meanwhile, the variation in pH 8 and 11 shows a color fading. The results of measurement of the initial pH were 7.4 ± 0.0 and the final pH is 7.7 ± 0.28. The organoleptic test results showed that the fish was not fresh on the 4th day based on the assessment of appearance, smell, and texture (SNI 2729: 2013). The conclusion was that purple sweet potato anthocyanin extract can be used to detect the freshness of dory fillets.